Magnetic Resonance Imaging Findings of Sixth Cranial Nerve Palsies in Patients Presenting with Diplopia - Tanrivermis Sayit, Asli; Elmali, Muzaffer; Niyaz, Leyla; Pinar Gunbey, Hediye; Aslan, Kerim (Current Medical Imaging, 2018)
Aim: The aim of our study was to investigate the etiology of patients presenting with double vision due to sixth cranial nerve palsy, and evaluate the relationships between the sixth cranial nerve and vascular structures, with Constructive Interference in a Steady-State (CISS) sequence. Materials and Methods: For this study, we evaluated the brain and orbital Magnetic Resonance Imaging (MRI) of 26 patients retrospectively, who were diagnosed with binocular diplopia associated with sixth nerve palsy between 2011 and 2016. The MRI images were assessed for those pathologies that can cause diplopia. Additionally, the cisternal segment of the sixth cranial nerve was assessed with CISS sequences for possible vascular contact or compression. Results: Nine of the 26 patients were over 50 years old, with medical histories of diabetes mellitus, hypertension, and hyperlipidemia/hypercholesterolemia. Microvascular angiopathy was considered for diagnosis in those patients with sixth cranial nerve palsy, while the medical history was normal in 17 of these 26 patients. Brain and orbital MRIs were used to detect any cavernous sinus pathology and/or dural sinus vein thrombosis; however, the MRIs were normal in 9 of 17 patients with sixth cranial nerve palsy. Therefore, vascular compression and/or contact were detected in these patients using the CISS sequence, because diplopia can be caused by vascular contact or compression of the sixth cranial nerve. Conclusion: Patients with complaints of double vision and normal brain and orbital MRIs should be evaluated using CISS sequences to show the relationships between the sixth cranial nerve and vascular structures.
Keywords: CISS